PSXI-34 Supplementation of grazing Nellore beef heifers during mid-to-late gestation as a strategy to improve skeletal muscle development of the offspring - Paula, Rones G De (J Anim Sci, 2019)
The aim of this study was to evaluate supplementation effects of grazing heifers during mid-to-late of gestation on skeletal muscle development and performance of the progeny until weaning. One hundred and eighty Nellore beef heifers confirmed pregnant (timed AI) to a single sire were allotted to a completely randomized design with 2 treatments. Ninety heifers were fed only mineral (control) and the other 90 were fed a protein supplement (44.5% CP, 0.15% BW) from 90 to 274 days of gestation. Cows were grazed on Urochloa brizantha cv. Marandu pastures (5% CP and 64% NDF). At calving, cow–calf pairs were commingled and grazed on the same pasture until weaning. At 30 days after birth, a biopsy was performed to obtain samples of skeletal muscle tissue (Semitendinosus) from calves to determine the number and size of muscle ﬁbre. Least squares mean for all data were computed using PROC MIXED of SAS (SAS Inst. Inc., Cary, NC). Calves from heifers supplemented with protein had greater birth BW (P < 0.001), ADG (P = 0.0147) and BW at 155 d (P = 0.0016) compared with calves from heifers not supplemented. However, calf BW at weaning (P = 0.1508) and gain from birth to weaning (P = 0.1446) did not differ. On the other hand, calves born from dams supplemented with protein had greater muscle ﬁbre number (P = 0.0262), larger diameter of the fiber (P < 0.001), and smaller diameter of the fiber (P < 0.001) compared with calves from heifers not supplemented, although did not differ for mean fiber diameter (P = 0.8079). Fiber volume, fiber perimeter, and volume/area ratio were also affected (P < 0.001) by prepartum supplementation, and were greater on calves whose dams were fed with protein. In conclusion, supplementation of pregnant Nellore heifers with protein during the dry season improves calf birth BW, and promotes hyperplasia and hypertrophy in the skeletal muscle of the offspring. [Image: see text]